Evaluating the quality of evidence of clinical interventions for children aged 6 to 12 years old with ADHD: a systematic review - Tan, Ching Wen (Nanyang Technological University, 2023)
Attention deficit hyperactivity disorder (ADHD) is one of the most commonly diagnosed disorders in childhood. Children with ADHD have inattention and/or hyperactivity-impulsivity problems. In recent years, the rise in diagnosis of ADHD has resulted in increased research in novel treatments to treat ADHD symptoms. Therefore, this systematic review gathers and evaluates the quality of evidence from recent studies that analyse the efficacy of existing and novel clinical interventions for children with ADHD, aged 6 - 12. Following a pre-registered review protocol, studies were identified from 2012 - 2022 in the digital repository, PubMed. A total of 3899 unique studies were gathered but only eleven studies met the inclusion criteria and were included in the qualitative analysis. Out of the eleven studies, only two studies are deemed to have “sufficient” evidence to support their findings on the efficacy of clinical interventions for ADHD. However, the two studies proceeded to score poorly on other additional quality indicators. Overall, the quality of evidence for clinical intervention studies on children with ADHD is poor, especially so for novel interventions. Novel interventions tend to be poorly designed and biassed. Future studies should work on improving the quality of evidence for clinical interventions, especially novel interventions, and researchers should improve future research practices outlined in the study.